Implementation of Community Service in Preserving Traditional Games - Dinda Restya; Mila Thohirotul Ulya; Dewi Anjani; Titin Sunaryati (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
This community service program was implemented in Desa Jatireja, Kecamatan Cikarang Timur, Kabupaten Bekasi. The aim of holding this community service is to introduce the heritage of traditional games to children as the nation's future generation in the future. The results of this PKM activity are described through the role of the literacy community in socializing literacy packaged creatively for children through the process of introducing types of traditional games